Genebank accessions sub-setting tool: IPSR Innovation Profile - Kehel, Zakaria; Ramírez Villegas, Julián Armando; Obreza, Matija; Rabil, Christelle; Aouzal, Khadija; Mora, Brian; García, Juan Camilo; Sotelo, Humberto Steven (2022)
Breeders are forced to seek the variation they require from genetic resource collections conserved in genebanks. The challenge when searching specific traits from genebanks is that resources to search for a given trait are often such that only a relatively small subset of the available genebank can be evaluated. Thus, to be effective, a strategy is required to identify the smallest possible subset of germplasm to evaluate whilst increasing the chances of capturing the sought-after variation.Genesys currently holds more than 4 million genebank accessions from 462 institutes and is accessed by users to order germplasm. From these, around 768,576 accessions are held at CGIAR genebanks. Identifying the correct set of accessions to respond to these requests adequately can be time-consuming.The subsetting tool allows to develop and implement data mining techniques for subsetting germplasm accessions, thus helping address germplasm requests more effectively and efficiently. The sub-setting is based on indicators for historical climate information, soil information and specific per crop regarding stresses. This web tool allows users to compose the needed subsets and order them directly from genebanks in Genesys. In the tool, a user identifies a series of potential subsets using data and analytics and then selects the subset of accessions that best suits their interest. For example, amongst four potential subsets, they may select the subset with accessions grown in the driest places.